Freshwater gastropod diversity in the selected lotic environment, Betong, Sarawak, Borneo - Anderson Bidat,; Abdulla Al-Asif,; Amy Halimah Rajaee,; Hadi Hamli, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Freshwater Gastropoda can be considered as the biological indicator in ecosystems such as rivers, streams, lakes, and ponds. The objectives of this study are to identify freshwater gastropod species, diversity, and distribution along Sungai Penebak, Sungai Nanga Tiga, and Sungai Kabo in the Betong division. The study was conducted on 10 November 2020. A 50 m transect was laid on the riverbank of all three stations. The existing specimens were counted and collected from each sampling point and stored were taken to the laboratory for species identification. The diversity index and morphological study of freshwater gastropods were performed. Five species of freshwater gastropods belonging to four families were discovered. The five species of freshwater gastropods consisted of Sulcospira pageli, which shows great abundance, followed by Clea nigricans, Brotia costula, Pila ampullacea, and Vittina pennata. The diversity indices of collected Gastropoda species from the different stations, for instance, Shannon-Weiner diversity index (H’), Pielou’s evenness index (J’), and Margalef’s richness index were assessed; where station 3 showed higher diversity of Gastropoda compared to other two stations. The information presented in this paper might be helpful for ecological wealth studies and considered as the baseline data for the stream ecosystem in Sarawak, Malaysia.